Genetic and environmental influences on cord blood atopic markers and on atopic sensitisation in infancy - Haus, Matthias (Department of Paediatrics and Child Health, 2018)
HISTORICAL PERSPECTIVE: It has recently been shown that intensive prophylactic dietary and environmental control measures during early infancy may reduce the incidence and/or postpone the onset of atopic disease. In order to institute this prophylactic regime, early identification of the infants genetically "at risk" for atopic disease is essential, since sensitisation begins at birth, or even during intra-uterine life. European and Scandinavian studies have shown that a raised concentration of cord blood serum immunoglobulin E (CBsIgE) is an excellent predictive marker for the subsequent development of atopic disease. Other potential predictive atopic markers such as cord blood eosinophils, platelets and anti-cow's milk serum IgG have also been suggested as having possible predictive relevance for newborns in terms of the development of subsequent atopic disease. PROBLEM DEFINITION: Most of the work in this field has been done on Caucasian neonates, in Westernised, First World countries. In South Africa, it has been shown that the Black adult ethnic group has serum immunoglobulin E concentrations (sIgE) which are significantly higher than that found in the South African White adult ethnic group. Furthermore, it has been suggested that the elevated sIgE in the adult Blacks may be raised independently of allergic disease. It is, therefore, important to ascertain whether this elevation of sIgE in Black South African adults is evident already at birth in the cord blood sera of Black South African newborns. If so, it is imperative to ascertain whether any such elevation is reflective of a high genetic load for atopy in these Black newborns, and furthermore whether these Black newborns are consequently "high-risk" for the development of subsequent atopic disease, as has been previously reported in the literature for White newborns. Arising from an awareness of these specific South African problems, the following hypothesis was developed. HYPOTHESIS: The hypothesis states that: "Black South African newborns without an atopic family history (aFH) have significantly higher CBslgE values than similar White and Mixed newborns. An aFH does not influence the CBsIgE values in the Black newborns, as it does in the White and Mixed newborns. The CBsIgE values in Black newborns are not, furthermore, predictive for the development of subsequent atopy in infancy, as they are in the other ethnic groups". A description of the three South African ethnic groups considered in this study is provided in Section IV, (Pg. 74). AIMS OF THE STUDY: The aims of the study were three-fold: 1. To test the hypothesis. 2. To assess the relevance of alternative cord blood markers (eosinophils, platelets and anti-cow's milk serum IgG) as predictive atopic markers in each of the three ethnic groups. 3. To provide epidemiological information with regard to genetic and environmental influences on CBslgE, cord blood total eosinophil counts (CBTEC's) cord blood platelet counts (CBPlC's) and cord blood anti-cow's milk serum IgG concentrations (CBacmlgG).